THE POLITICS OF MINING LAW IN ENVIRONMENTAL LAW ENFORCEMENT SYSTEM IN REGIONAL AUTONOMY ERA - afif syarif (Faculty of Law, Universitas Jenderal Soedirman, 2018)
The politics of mining law plays an important role in the management of mining business in the re-gion. In addition, local government have the authority in the environmental management to support the environmental laws enforced optimally in the area. The problem is, the politics of mining law affects the environmental law enforcement in the mineral and coal mining management. This condi-tion is an issue of the environmental law enforcement in the field of coal mining business in enfor-cing the regional autonomy. It seems that some of the central authorities are delegated to the re-gions by which the position of local chiefs becomes very powerful. Meanwhile, the application of le-gal norms in the environmental law enforcement is still ambiguous in terms that the Minerba law does not clearly regulate the responsibility of administrative law and criminal law. This condition is caused by the change of centralized government system to be decentralized government system which then has implication on the environmental law enforcement in the field of coal mining in the region. Keywords: Mining; Environmental Law, Regional Autonomy.